2016
DOI: 10.2298/tsci141111109h
|View full text |Cite
|
Sign up to set email alerts
|

Building envelope influence on the annual energy performance in office buildings

Abstract: The objective of the research is to determine the quantitative influence of building envelope on the annual heating and cooling energy demand in office buildings demonstrated on a reference office-tower building located in city of Novi Sad, Serbia. The investigation intended to find preferable and applicable solutions for energy performance improvement in currently inefficient office buildings. A comparative and evaluative analysis was performed among the heating energy expenses and simulated values from the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 13 publications
0
17
0
2
Order By: Relevance
“…Unlike conventional material for façade materialization, vegetation walls do not absorb the received solar radiation. Since the value of the coefficient of heat transfer of the façade wall with the added vegetation wall has been reduced, it can be concluded that the experimental measurements yielded the expected results [12,13]. The selection of the system of greening plays a key role in the optimization process, because it allows its performance to increase or decrease the percentage contribution of the selected module in the process of optimizing the façade coating [14].…”
Section: Discussionmentioning
confidence: 99%
“…Unlike conventional material for façade materialization, vegetation walls do not absorb the received solar radiation. Since the value of the coefficient of heat transfer of the façade wall with the added vegetation wall has been reduced, it can be concluded that the experimental measurements yielded the expected results [12,13]. The selection of the system of greening plays a key role in the optimization process, because it allows its performance to increase or decrease the percentage contribution of the selected module in the process of optimizing the façade coating [14].…”
Section: Discussionmentioning
confidence: 99%
“…To stabilize the frame, 1 mm thick aluminum profiles were included along the contour. The glazing materials were not relevant for the thermal simulation because most of the energy transmitted through windows was assumed to occur by radiation [23]. Reference model without the PCM layer, was compared with other three PCM formulations (EC-PCM40, EC-PCM40-BN10, and EC-PCM40-CNF2) included in the external walls and roof construction.…”
Section: Dwelling Modelmentioning
confidence: 99%
“…Several studies have demonstrated that the envelope of a building influences thermal demand significantly. The envelope construction has great impact in heating and cooling demands and its optimization provides considerable benefits in terms of energy savings and increases energy efficiency of a building [21][22][23][24]. The envelope implementation of materials with high heat capacity is an effective way to generate energy efficient buildings [25].…”
Section: Introductionmentioning
confidence: 99%
“…The transfer function method of calculation was done in two steps: calculating heat gains through the elements of the covering, through walls, roof, wherein dominates the heat passage. Heat transfer originates from outer air heated to a relatively high temperature and solar radiation, whose influences are joined in the air temperature [13]. Heat transfer [14] is done by convecting the air inside the room, either directly from the inner surfaces, or indirectly, when the matter of heat transfer by radiation and the effects of accumulation are concerned.…”
Section: Applied Simulation On a Residential Buildingmentioning
confidence: 99%